(untitled) (Journal of Material Science and Technology Research, 2020)
This present research work aims at fabrication of AA7068 metal matrix composite reinforced with a different weight percentage of Al2O3, TiO2 and Cu (0 wt.%, 2 wt.%, and 4 wt.%) nanopowders through mechanical alloying of 30 hrs which is produced using powder metallurgy route. The consolidation pressure of 500 MPa was applied for compaction of the composite and sintered at a temperature of 600°C for two hrs in the presence of argon gas flow. An XRD result reveals that there are no intermetallic compounds formed in the milled powder after 30 hr of mechanical alloying. The reinforcement particles were well embedded and uniformly distributed in matrix composites was confirmed by bright-field emission transmission electron microscopy (FETEM) image and selected area diffraction (SAD) ring pattern. From the DSC curve of AA 7068–2.0 wt. % Al2O3, TiO2 and Cu nanocomposite powders after 30 hrs of mechanical alloying., the endothermic peak at 536.85°C corresponds to the melting of aluminium which was followed by a steady-state exothermic reaction at 579.51°C was obtained. The green density and sintered density of prepared nanocomposites were calculated and compared. Brinell hardness test has been conducted and the maximum value of 192 BHN was obtained by adding a weight percentage of 2 wt. % of Al2O3, TiO2 and Cu particles.